CEU Graduation Ceremony 1999 - Opening Remarks, Alumni Speaker, Student Speaker
Recording of the CEU Graduation Ceremony of 1999. Contains the Opening of the Ceremony and part of of the conferment of degrees upon CEU's class of 1999. Introductory words by Pro-Rector Sorin Antohi. Opening remarks by CEU's President and Rector Josef Jarab and Lord Dahrendorf of the CEU Board of Trustees. Speeches by alumni speaker Kristina Plavsak (IRES 1995) and student speaker Roman Didenko (Political Science 1999). The recording contains also the announcement of the graduating students' selection of Loránd Ambrus-Lakatos as ”Professor of the Year.”